Neurodevelopmental Outcome of Prenatally Diagnosed Boys With 47, XXY (Klinefelter Syndrome) and the Potential Influence of Early Hormonal Therapy. Issue 1 (January 2021) - Samango-Sprouse, Carole A.; Tran, Selena L.; Lasutschinkow, Patricia C.; Sadeghin, Teresa; Powell, Sherida; Mitchell, Francie L.; Gropman, Andrea
Abstract : (Abstracted from Am J Med Genet 2020;182A:1881–1889) 47, XXY (Klinefelter syndrome) is characterized by disruption in neurodevelopment, the endocrine and musculoskeletal systems, and brain morphology. It is also associated with an increased risk of asthma, infertility, decreased muscle tone, emotional lability, and decreased libido.